Particle emission and thermal efficiency analysis of a diesel vehicle using biodiesel and a platinum metallic partial-flow particulate filter - Huy Quang Dang; Mi Zwe Mon Phyo; Poonnut Thaeviriyakul; Plan Teekatasn Cosh; Mek Srilomsak; Therdsak Petblengsri; Ittipol Pawarmart; Sompong Srimanosaowapak; Hidenori Kosaka; Preechar Karin (Alexandria Engineering Journal)
Harmful emissions from diesel vehicles, particularly unmodified ones, pose significant concerns for human health and the environment, underscoring the urgency to address these issues. This study investigated the effects of commercial fuels, B10, B20, and biodiesel B100, used with a metallic partial-flow catalyzed diesel particulate filter (P-CDPF), on a light-duty unmodified diesel vehicle's thermal efficiency and emissions characteristics. The initial test was conducted on a chassis dynamometer to measure the fuel flow rates at three different engine speeds, 1500, 2000, and 2500 rpm, with four loads, 84, 112, 140, and 160 Nm. This was done to evaluate brake-specific fuel consumption and brake thermal efficiency under steady-state conditions. The second test followed the new European driving cycle to examine emission factors of regulated pollutants under both urban and highway driving conditions. The results indicated that BSFC values increased with the biodiesel ratio in the blends, attributed to lower heating values. However, higher oxygen contents with increasing biodiesel ratios led to more complete combustion and improved brake thermal efficiency. Installation of a P-CDPF had a minimal impact, resulting in less than a 3.4% increase in the BSFC and a 1% decrease in brake thermal efficiency across all tested fuels, owing to its relatively low pressure drop. Increasing the biodiesel ratio from B10 and B20 to B100 resulted in reductions of up to 32% of particulate mass and 45% of particulate number in vehicle emissions. P-CDPF installation further reduced particulate mass by over 60% and particulate number by 36% across all tested fuels, demonstrating its effectiveness in trapping and passively oxidizing particulate matter. Furthermore, the P-CDPF significantly reduced harmful gases with addition of a catalytic coating. A combination of a P-CDPF and commercial biodiesel fuels emerges as an effective solution for reducing regulated emissions from unmodified diesel vehicles.